On the genus Tenagogonus Stål (Hemiptera: Heteroptera: Gerridae) from India with a description of a new species - Jehamalar, E. Eyarin; Chandra, Kailash (Zootaxa, 2013)
Tenagogonus venkataramani sp. nov. from Great Nicobar Biosphere Reserve (GNBR), Andaman and Nicobar Islands, India, is described and compared with allied species. Morphological notes on T. ceylonensis Hungerford and Matsuda, 1962, and T. nicobarensis Andersen, 1964, known from India, are presented along with distribution maps of these three Indian species.